International financial market integration, asset compositions, and the falling exchange rate pass-through - Enders, Almira; Enders, Zeno; Hoffmann, Mathias (Journal of international economics, 2017)
This paper provides an explanation for the observed decline of the exchange rate pass-through into import prices by modeling the effects of financial market integration on the optimal choice of the pricing currency in the context of rigid nominal goods prices. Contrary to previous literature, we explicitly take into account the interdependence of this decision with the optimal portfolio choice of internationally traded financial assets. Following financial integration, agents use equity, additional to bonds, to hedge against shocks. The resulting optimal portfolio includes a higher share of bonds denominated in foreign currency and impacts the correlation structure of costs and sales in such a way that producers move towards more local-currency pricing. Both predictions are in line with novel empirical evidence.